ANALYSING THE IMPACT OF ECONOMIC AND EMPLOYMENT GROWTH ON THE REDUCTION OF THE POOR POPULATION IN JAMBI - Nengsih, Titin Agustin; Yulianti, Risty; Kirana, Sashi Syalwa; Almansyah, Almansyah; Majid, M Nazori; Usdeldi, Usdeldi; Rahma, Sri; Mutia, Agustina (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Employing information collected between 2019 to 2021, this study analyses the impact of economic growth and job expansion on a reduction in the amount of disadvantaged individuals in Jambi. The present research employed a quantitative methodology, meaning that multiple linear regression statistics were used to examine numerical data. Using secondary data from the BPS (Central Statistics Agency), the implications of employment, economic growth, and the poor population variable were investigated. The results of the study indicate that although the economic growth variable has no apparent beneficial effects on the impoverished population, it has significant consequences on people.